Outcomes of robotic versus laparoscopic surgery for mid and low rectal cancer after neoadjuvant chemoradiation therapy and the effect of learning curve. Issue 40 (October 2017) - Huang, Yu-Min; Huang, Yan Jiun; Wei, Po-Li
Abstract : Abstract: Randomized controlled trials have demonstrated that laparoscopic surgery for rectal cancer is safe and can accelerate recovery without compromising oncological outcomes. However, such a surgery is technically demanding, limiting its application in nonspecialized centers. The operational features of a robotic system may facilitate overcoming this limitation. Studies have reported the potential advantages of robotic surgery. However, only a few of them have featured the application of this surgery in patients with advanced rectal cancer undergoing neoadjuvant chemoradiation therapy (nCRT). From January 2012 to April 2015, after undergoing nCRT, 40 patients with mid or low rectal cancer were operated using the robotic approach at our institution. Another 38 patients who were operated using the conventional laparoscopic approach were matched to patients in the robotic group by sex, age, the body mass index, and procedure. All operations were performed by a single surgical team. The clinicopathological characteristics and short-term outcomes of these patients were compared. To assess the effect of the learning curve on the outcomes, patients in the robotic group were further subdivided into 2 groups according to the sequential order of their procedures, with an equal number of patients in each group. Their outcome measures were compared. The robotic and laparoscopic groups were comparable with regard to pretreatment characteristics, rectal resection type, and pathological examination result. After undergoing nCRT, more patients in the robotic group exhibited clinically advanced diseases. The complication rate was similar between the 2 groups. The operation time and the time to the resumption of a soft diet were significantly prolonged in the robotic group. Further analysis revealed that the difference was mainly observed in the first robotic group. No significant difference was observed between the second robotic and laparoscopic groups. Although the robotic approach may offer potential advantages for rectal surgery, comparable short-term outcomes may be achieved when laparoscopic surgery is performed by experienced surgeons. However, our results suggested a shorter learning curve for robotic surgery for rectal cancer, even in patients who exhibited more advanced disease after undergoing nCRT.